Efeito da aplicação de diferentes concentrações de ácido etilenodiamino tetra-acético (EDTA) na adesão de pinos de fibra de vidro ao canal radicular - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The aim of the present study was to compare the effect of applying EDTA in two concentrations (17% and 24%) on the cementation of glass fiber posts (GFP) to the root canal, using conventional or self-adhesive resin cements. For this purpose, 156 permanent uniradicular teeth were selected, which had theis crowns removed and root canals treated endodontically. After preparing de conduits, the adhesive procedures were divided into two experiments, according to the type of adhesive strategy for resin cement. For Experiment 1, the Single Bond Universal and Ambar Universal adhesive systems, used in self-etch form, with their respective conventional resin cements RelyX Ultimate (RT) and Allcem Core (AC), were used. For Experiment 2, self-adhesive resin cements RelyX U200 (RL) and Multilink Speed (ML) were selected. The experimental groups for the two experiments were the same: irrigation with distilled water (control group), EDTA 17% and EDTA 24%. In each root, 2mL of the solution defined in the experimental group was irrigated, and, even with the wet surface, a disposable brush was applied actively for 30s in each conduit. After these procedures, the GFP were cemented to the root canal according to the recommendations of each manufacturer. In this study, six extra roots were selected for the analysis of energy dispersion X-ray spectroscopy (EDS) to assess mineral composition and conditioning pattern. For Experiment 1, eight roots were selected for the test of bond strength by push-out test (BS), and four for the analysis of nanoleakage (NL). In Experiment 2, 8 roots were selected for the push-out test and 3 for the Vickers microhardness test (VHN). The data from the experiments were analyzed statistically by means of two-way analysis of variance (ANOVA) and Tukey's test for contrast of means at a significance level of 5% (p = 0.05). For conventional cements, the application of EDTA solutions did not interfere with the BS values (p> 0.05) and increased the NL values (p <0.05). For selfadhesive resin cements, groups cemented with RL decreased the bond strength values when irrigated with EDTA 24%. For ML cement, there was no difference between irrigating groups. The microhardness values decreased significantly with the use of EDTA 24%, in both self-adhesive cements. As it increases a clinical step in the cementation protocol and does not show significant benefits from the adhesion of GFP to the root canal, the use of EDTA prior to cementation is not indicated.
Keywords: Ácido Edético; Cimentos de Resina; Dentina; Força Compressiva; Técnica para Retentor Intrarradicular; Edetic Acid; Resin Cements; Dentin; Compressive Strength; Post and Core Technique; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA